MEMOTRET TIPOLOGI TASAWUF KONTEMPORER - Mahjuddin (Al'Adalah, 2015)
Contemporary Tasawuf are the spiritual activities that combines between religious activities and social activities, so that every man of participating in these activities, it is hoped that he could obtain Sufism value and social value of community. Tasawuf contemporary done with remembrance and read asmaul husnah, and continued with the collection infaq from participants tasawuf as the fund would go to very poor or those who need it. Therefore, tasawuf contemporary can grades create a spiritual and social values. Contemporary Tasawuf always linked daily life in the spiritual acts; for example tasawuf in economic activity, tasawuf in domestic activities, tasawuf in governmental activities, tasawuf in law enforcement, tasawuf in education, so tasawuf available in the raising of mental health.